RISK MANAGEMENT MECHANISMS IN INNOVATION FINANCING (American Journal of Interdisciplinary Research and Development, 2025)
This article analyzes modern financial mechanisms for financing startup projects, including incubators, accelerators, and crowdfunding platforms. During the study, the practical experience of such large international initiatives as Y Combinator, Techstars, 500 Global, Kickstarter, Indiegogo, Wefunder was studied. These mechanisms will reveal their role in supporting young entrepreneurship and innovative ideas, expanding opportunities for attracting investments, and ensuring the sustainable development of the startup ecosystem. Also, the prospects for the implementation of these mechanisms in the conditions of Uzbekistan and proposals for the development of a national startup environment have been developed.